Quantitative factor analysis of fixed asset impairment: a multi-case study of state-owned enterprises in the pharmaceutical and construction sectors - Bagas Anggi Winata; Zuhrinal M Nawawi; Yenni Samri Juliati Nasution (Pusat P2M Politeknik Negeri Batam, 2026)
This study examines the quantitative factors influencing fixed asset impairment in two Indonesian state-owned enterprises (BUMN) operating in the pharmaceutical and construction sectors under PSAK 48. The research problem focuses on declining profitability, high leverage, and negative operating cash flows that potentially reduce asset value. The objective is to analyze the relationship between Return on Assets (ROA), Debt to Asset Ratio (DAR), Fixed Asset Turnover (FATO), and Cash Flow from Operations (CFO) with asset impairment risk. A descriptive-comparative quantitative approach was employed using multi-case study data from 2022–2024 financial reports. The findings reveal that persistent negative CFO and high DAR are the main indicators of asset impairment risk, while the implementation of PSAK 48 remains inconsistent. This study concludes that a financial ratio-based quantitative model can serve as an early detection tool for asset impairment in BUMN. This research is limited to a sample of state-owned enterprises and certain quantitative variables, but has implications for increasing the accuracy of asset impairment testing in accordance with PSAK 48, with the novelty of cross-sector multi-case analysis.